Malaria Recent Advances and New Perspectives - Paolo Piccaluga, Pier (Infectious Diseases, 2023)
Malaria remains a leading cause of morbidity and mortality worldwide. Children in Africa and selected regions of Asia and Southern America are especially widely affected. Written by expert research teams, this book describes different aspects of the epidemiology, pathobiology, diagnosis, prevention, and treatment of malaria. Chapters highlight current research as well as the gold standards for diagnosis and treatment of the disease, examining recent advances, remaining pitfalls, and novel ideas about prophylaxis and therapy.